PEMBUATAN DAN UJI KINERJA MESIN PENGADUK ADONAN GELAMAI UNTUK PENINGKATAN PRODUKSI GELAMAI - Irwan A; Edi Syafri; Evawati Evawati; Perdana Putera (Universitas Andalas, 2015)
Gelamai, a traditional well-known food in Indonesia, was produced through hands of high-skill workers. Since its production needs about 5 to 6 hours it is need a reliable machine to assist the mixing process, to reduce the dependence on labor and also to maintain the homogeneity of production. This research was conducted to implement gelamai kneading machine since the lack appropriate technologies in this industry to overcome this problem is by applying the gelamai mixing machine. The performance test has been done at “NITA” as industrial partner. Specification of the machine is 120x20x130 cm in dimensions. Gelamai kneading machine gelamai uses one HP electric motor power source. Capacity of the machine is 7.26 Kg per hour. With the interest rate of 18% per year it is found that the basic cost is Rp. 2,001 per kilogram.. The success of this research also spur the development of small industries especially Gelamai industry in Payakumbuh that can create new jobs for the community such as the growth of new machine and equipment workshop and Gelamai home industry.Keywords: mixing machine, gelamai, and traditional food industry.